2010
DOI: 10.24084/repqj08.333
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Antenna Effect of Photovoltaic Modules

Abstract: Abstract.We have investigated the reaction of photovoltaic cells to external electromagnetic fields in a frequency range of 10 Hz to 1 GHz. Outdoor recordings of received RF noise from the ambient were sampled for different solar cells and modules and compared with the reception of a simple whip antenna which represents a monopole for electromagnetic fields. Additionally in the laboratory well defined signals were generated and their reception was investigated depending on geometrical factors of the cells, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Erel concluded that the short-circuit current and the open-circuit voltage decreased under the simultaneous effects of both electric and magnetic fields. Drapalik et al [2] studied crystalline photovoltaic cells as both receivers and emitters of electromagnetic waves. As receivers, they concluded that the reception of electromagnetic radiation depends linearly on the cell area, at least at low frequencies (below 10 MHz).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erel concluded that the short-circuit current and the open-circuit voltage decreased under the simultaneous effects of both electric and magnetic fields. Drapalik et al [2] studied crystalline photovoltaic cells as both receivers and emitters of electromagnetic waves. As receivers, they concluded that the reception of electromagnetic radiation depends linearly on the cell area, at least at low frequencies (below 10 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…These installations are sources of radio waves that may interact with solar photovoltaic installations, hence raising the issue of electromagnetic compliance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Drapalik et al [2] studied crystalline photovoltaic cells as both receivers and emitters of electromagnetic waves. As receivers, they con- cluded that the reception of electromagnetic radiation depends linearly on the cell area, at least at low frequencies (below 10 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…But it seems that photovoltaic modules and the silicon solar cells of these photovoltaic modules are sensitive to the electromagnetic field generated by electromagnetic emission sources. So, interaction between photovoltaic modules and electromagnetic fields or radiation have to be taken into account [2].…”
Section: Introductionmentioning
confidence: 99%
“…So called quasi-steady-state, QSS conditions during transient recording are widely applied [4,5]. In the electrical circuit formed by the photovoltaic array and the connected power conditioning unit the modules act as a low pass filter for the transmitted noise [6].…”
mentioning
confidence: 99%